2006
DOI: 10.1111/j.1398-9995.2006.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of cytotoxic T cells in allergic asthma correlates with total serum immunglobulin E

Abstract: In allergic asthma, cytotoxic T lymphocyte subsets of a more differentiated phenotype are significantly decreased and this is correlated to serum immunglobulin E levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Exercise-induced bronchoconstriction, for example, is a common and distressing clinical feature of most children with asthma (22) characterized by airway inflammation. We found that exercise affected a number of asthma-related PBMC genes (e.g., TBX21, CCL5, PTGDR, GZMA), which could play a role in asthma pathogenesis ranging from altering susceptibility to atopy in general to factors that govern the recruitment and activation of inflammatory cells (23-26). Whether levels of physical activity and fitness can alter the PBMC function in health and disease in children by influencing gene expression and translation has not been determined.…”
Section: Discussionmentioning
confidence: 97%
“…Exercise-induced bronchoconstriction, for example, is a common and distressing clinical feature of most children with asthma (22) characterized by airway inflammation. We found that exercise affected a number of asthma-related PBMC genes (e.g., TBX21, CCL5, PTGDR, GZMA), which could play a role in asthma pathogenesis ranging from altering susceptibility to atopy in general to factors that govern the recruitment and activation of inflammatory cells (23-26). Whether levels of physical activity and fitness can alter the PBMC function in health and disease in children by influencing gene expression and translation has not been determined.…”
Section: Discussionmentioning
confidence: 97%
“…The Th2 cytokine interleukin (IL)-4 is able to induce a poorly cytolytic CD8 + T cell phenotype [15]. Reduced percentages of granzyme B + and/or perforin + CD8 + T cells have been detected in the peripheral blood of asymptomatic patients suffering from Th2-related diseases such as allergic asthma, atopic dermatitis and/or allergic rhinoconjunctivitis [3,4,16], suggesting that the predominant atopic milieu in such patients might influence CD8 + T cell development. Our present data provide evidence that not only is cytotoxic protein synthesis inhibited in an atopic milieu, but also activation and terminal differentiation of CD8 + T cells to an effector-like type.…”
Section: Discussionmentioning
confidence: 99%
“…Current opinion links atopic asthma to an increase in T helper 2 (Th2) factors and a decrease in Th1 factors, suggesting a delayed clearance of respiratory viral infections [2]. Accordingly, in previous studies an association of the Th2 diseases allergic asthma, atopic dermatitis and allergic rhinoconjunctivitis with reduced expression of the cytotoxic proteins granzyme B and/or perforin in peripheral blood CD8 + T cells has been described [3,4]. These cytotoxic proteins, especially granzyme B, are synthesized by differentiated CD8 + T cell subsets of the memory/effector and effector type but not by classical memory CD8 + T cells [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, reduced percentages of GrBpositive CD4 + , CD8 + and CD16 + /CD56 + T lymphoyctes have been detected in peripheral blood of patients suffering from allergic asthma. 18 IL-4 is a key cytokine in the development of allergic diseases. IL-4 concentrations are elevated at sites of allergic inflammation.…”
Section: Regulatory Cd4mentioning
confidence: 99%